Serum prolidase, urotensin-2 and nesfatin levels in patients with compensated or uncompensated cirrhosis (Annals of Medical Research, 2021)
Aim: To assess the feasibility of serum prolidase, urotensin-2, and nesfatin measurements as diagnostic and follow-up markers of compensated or uncompensated cirrhosis. Material and Methods: The study included 97 cirrhosis patients and 51 healthy individuals who were admitted to the Internal Medicine and Gastroenterology Clinics of Harran University Research and Application Hospital between May 2014 and June 2015. Patients with esophageal variceal bleeding, ascites, hepatic encephalopathy were considered as having decompensated cirrhosis. Blood samples obtained from patient and control groups were stored at -85 C. ELISA methodology was used for measurements.Results: A total of 97 cirrhotic patients (43 with compensated and 54 with decompensated cirrhosis) with a median age of 53.98±15.67 years (range: 19-89) were included in the study. Serum prolidase, urotensin-2, and nesfatin in patients with cirrhosis compared to 51 healthy controls. Serum prolidase levels were significantly lower in the overall group of patients with cirrhosis as well as in the decompensated cirrhotic patients as compared to controls (p0.001). Urotensin-2 was significantly lower in the compensated cirrhosis group than in controls (p0.05). Nesfatin was significantly higher in the overall and decompensated cirrhotic than in controls (p0.05).Conclusion: Our results suggest that serum prolidase levels can be used as a marker for diagnosis and follow-up in patients with decompensated cirrhosis and that urotensin-2 may play a role in the pathogenesis of cirrhosis. Again, a higher nesfatin level in the overall and decompensated cirrhosis patients was suggestive of its potential role in the development of loss of appetite and cachexia characteristic of advanced cirrhosis as well as a role as a potential marker.Keywords: Cirrhosis; prolidase; urotensin-2; nesfatin.
Keywords: Cirrhosis; prolidase; urotensin-2; nesfatin.